The Effectiveness of Fly Control in Reducing the Spread of Disease: A Review - Abdul Rahman (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Flies (Musca domestica) are synanthropic insects capable of transmitting pathogenic agents such as protozoa, helminths, viruses, fungi, and bacteria. Acting as mechanical vectors, they contribute to the indirect transmission of various diseases. Their presence often indicates poor environmental hygiene and poses significant health risks to surrounding communities. Flies can carry approximately 100 species of bacteria pathogenic to humans and animals. Fly control aims to prevent disease spread by reducing fly density through improvements in sanitation and environmental management. The application of natural and synthetic insecticides remains a widely practiced and effective strategy. Objective: This study aims to evaluate the effectiveness of various fly control methods in reducing the potential for disease transmission. Methods: A Systematic Literature Review (SLR) was conducted by collecting and analyzing articles from Google Scholar and ResearchGate, following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework. Articles published between 2020 and 2024 were reviewed using the keywords “flies,” “effectiveness,” and “control methods.” Results: The reviewed literature reported multiple effective approaches to reducing fly density, including the use of lime camphor mixtures, clove leaf extract, basil leaves, papaya leaves, chemical insecticides, mechanical trapping, and bait variation in fly traps. Conclusion: Flies play a critical role in transmitting diseases such as diarrhea, cholera, dysentery, and food poisoning. Effective fly control, supported by improved environmental sanitation, is essential to minimize the prevalence of flies and reduce the risk of disease transmission. Keywords: Indonesia, flies, effectiveness, control